Chemical Constituents and Biological Activity of Clausena excavata (Rutaceae) - Lim, Gin Keat (2005)
Ten chemical constituents were isolated from the investigations on the leaves of Clausena excavata (Rutaceae) collected from Jasin, Melaka. The structures of these chemical constituents were elucidated by using spectroscopic techniques, such as NMR, MS, GC, FTIR and UV, and also by comparison with the previous reports. The fresh fruits and leaves were also hydrodistillated to obtain the essential oils. The chemical constituents and the composition of the essential oils were identified by GC-MS analysis. Compounds isolated from the leaves of Clausena excavata afforded one new coumarin from Clausena excavata, denoted as clauslactone-R (121), two known coumarins, clauslactone-B (96) and scopoletin (8), five known triterpenes, friedelin (115), stigmasterol (116), β-sitosterol (117), 5(6)-gluten-3-one (118) and glutinol (5), together with one carbazole alkaloid suggested as, 2, 6-dihydroxy-4-(1’hydroxy-1’-methoxy-ethyl)-5-prenylcarbazole (120) and one triterpene proposed as, 23-ethyl-24-methyl-art-5,24-diene-3-one (119). The crude extracts and essential oils obtained from these plant materials were evaluated for their larvicidal, antimicrobial, antifungal and cytotoxic activities. The main components found in essential oils obtained from the fruits were β-caryophyllene (22.89%) and germacrene-D (15.49%); whereas leaf’s oil gave elemicin (65.02%) and methyl eugenol (12.95%) as its major components. Others minor components found in these essential oils were various terpenes. The insecticidal test for the crude extracts and essential oils yielded was conducted on the mosquito larvae Aedes aegypti revealed that the leave’s oil showed significant activity against the larvae, with LC50 value of 24.26µg/ml. The fruit’s oil and crude chloroform extract were highly active, with LC50 values of 51.03 and 55.10µg/ml, respectively; followed by crude hexane extract and crude ethyl acetate extract, with LC50 values of 82.46 and 77.92 µg/ml, respectively, which categorized as active against the larvae of Aedes aegypti. Both L-oil and F-oil were tested against four pathogenic bacteria, Bacillus subtillis, Salmonella typhimurium, Staphylococcus aureus and Pseudomonas aeruginosa; together with three fungi, Candida albican, Aspergillus ochraceaus and Sacchoromyces serevisiae. The antimicrobial and antifungal screening results showed that the fruit’s oil was moderately active, while leave’s oil was not active against all the microbes and fungi tested. The cytotoxicity screening shown that glutinol (5), 5(6)-glutin-3-one (118), clauslactone-B (96), clauslactone-R (121) and 23-ethyl-24-methyl-art-5, 24-diena-3-on (119) isolated were found to be inactive against HL-60 cell-line. Both Leave’s oil and Fruit’s oil were bioassay against various cell-lines, i.e. T-cell Acute Lymphoblastic Leukaemia Cells (CEM-SS), Human Ovarian Cancer Cells (CaOV3), Human Colon Adenocarcenoma Cells (HT 29), Hormone-Dependent Breast Cancer Cells (MCF-7) and Liver Cancer Cells (Hep-G2). However both essential oils were inactive against all these cell-lines used.